Sinergi Mobilitas dan Konservasi: Kolaborasi Toyota dan Geopark Kaldera Toba dalam Mendukung Pariwisata Berkelanjutan - Sinaga, Ayu Puspita Sari; Sembiring, Hermansyah (MARHALADO: Jurnal Pengabdian kepada Masyarakat, 2026)
Toba Caldera UNESCO Global Geopark is one of Indonesia's strategic tourism destinations with significant geological, ecological, cultural, and educational values. Sustainable management requires collaboration among government institutions, academia, business sectors, local communities, and media. This community engagement initiative proposes a collaborative partnership between the Provincial Government of North Sumatra, Karo Regency, Samosir Regency, the Toba Caldera UNESCO Global Geopark Management Agency, and Toyota Indonesia through Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) programs. The implementation methods include stakeholder coordination, participatory planning, environmental conservation, tourism mobility enhancement, community empowerment, and digital tourism development. The expected outcomes are improved tourism accessibility, increased community income, strengthened environmental conservation, enhanced tourist satisfaction, and sustainable regional economic growth.